A Cell-Based High-Throughput Screening Identified Two Compounds that Enhance PINK1-Parkin Signaling - Kahori Shiba-Fukushima; Tsuyoshi Inoshita; Osamu Sano; Hidehisa Iwata; Kei-ichi Ishikawa; Hideyuki Okano; Wado Akamatsu; Yuzuru Imai; Nobutaka Hattori (iScience, 2020)
Summary: Early-onset Parkinson's disease-associated PINK1-Parkin signaling maintains mitochondrial health. Therapeutic approaches for enhancing PINK1-Parkin signaling present a potential strategy for treating various diseases caused by mitochondrial dysfunction. We report two chemical enhancers of PINK1-Parkin signaling, identified using a robust cell-based high-throughput screening system. These small molecules, T0466 and T0467, activate Parkin mitochondrial translocation in dopaminergic neurons and myoblasts at low doses that do not induce mitochondrial accumulation of PINK1. Moreover, both compounds reduce unfolded mitochondrial protein levels, presumably through enhanced PINK1-Parkin signaling. These molecules also mitigate the locomotion defect, reduced ATP production, and disturbed mitochondrial Ca2+ response in the muscles along with the mitochondrial aggregation in dopaminergic neurons through reduced PINK1 activity in Drosophila. Our results suggested that T0466 and T0467 may hold promise as therapeutic reagents in Parkinson's disease and related disorders.